The Role of Emotional Regulation and Self-Efficacy toward Students' Academic Resilience - Annisa, Rahma Fitri; Nurfarhanah, Nurfarhanah; Firman, Firman; Hariko, Rezki (Journal of Educational, Health and Community Psychology, 2024)
Academic pressures lead students to experience stress and lack of adaptability. One of the issues is the lack of academic resilience, influenced by emotional regulation and self-efficacy. This research aims to depict the behaviors of academic resilience, emotional regulation, and selfefficacy among students of MTsN 4 Kota Padang, as well as their correlations. Conducted with a quantitative approach and descriptive correlational method involving 271 muslim students. Results indicate that emotional regulation and self-efficacy are at a moderate level, as well as academic resilience. There is a significant relationship between emotional regulation, self-efficacy, and academic resilience. The implication is that BK teachers can provide services to enhance emotional regulation and self-efficacy to reduce students' academic resilience